Eternalized fragments : reclaiming aesthetics in contemporary world fiction - Wang, W. Michelle (Cognitive approaches to culture., 2020)
"Bridges discussions of traditional aesthetics with contemporary neuroaesthetics and evolutionary psychology and analyzes texts from many cultural and national traditions (including Gabriel García Márquez, Kazuo Ishiguro, Arundhati Roy, Jeanette Winterson, Jennifer Egan, Italo Calvino, Flann O'Brien, and Alasdair Gray), identifying three dominant aesthetic modes pertinent to post-war fiction"--